2011
DOI: 10.1016/j.bbrc.2011.05.081
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1Ea induces vessel formation after injury and mediates bone marrow and heart cross-talk through the expression of specific cytokines

Abstract: The aim of this study was to investigate whether supplemental IGF-1Ea transgene expression induces activation of local cardiac and bone marrow stem cell population to mediate mammalian heart repair. In physiologic conditions, cardiac overexpression of the IGF-1Ea propeptide is associated with an enrichment of c-Kit/Sca-1 positive side population cells in the bone marrow and the occurrence of an endothelial-primed CD34 positive side population in the heart. This cellular profile is shown here to correlate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…The fact that the mIGF-1 cardiac transgene can elicit other systemic effects, such as an increase in the immune cell count and behavioral modification (better performance in a fear conditioning test) (3), underlie profound differences in the "circulome" of mIGF-1 Tg animals, depending on molecules secreted by CMs in a autocrine and/or paracrine fashion. In this respect, it has been shown that the cardiac mIGF-1 transgene is proangiogenic: it can trigger the production of cytokines that mobilize stem cells in the bone marrow to form new blood vessels (20). In the present study, we found that the effect of mIGF-1 on BP mediated by TRPA1 could be rescued by CM-specific depletion of SIRT1, which, in turn, was not associated with decreased cardiovascular performance (30).…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…The fact that the mIGF-1 cardiac transgene can elicit other systemic effects, such as an increase in the immune cell count and behavioral modification (better performance in a fear conditioning test) (3), underlie profound differences in the "circulome" of mIGF-1 Tg animals, depending on molecules secreted by CMs in a autocrine and/or paracrine fashion. In this respect, it has been shown that the cardiac mIGF-1 transgene is proangiogenic: it can trigger the production of cytokines that mobilize stem cells in the bone marrow to form new blood vessels (20). In the present study, we found that the effect of mIGF-1 on BP mediated by TRPA1 could be rescued by CM-specific depletion of SIRT1, which, in turn, was not associated with decreased cardiovascular performance (30).…”
Section: Discussionsupporting
confidence: 44%
“…PCR genotyping was performed using genomic DNA from tail biopsies. For in vivo inhibition of TRPA1 activity, mice were injected with the TRPA1 antagonist HC-030031 (20,50, and 100 mg/kg ip dissolved in 10% DMSO, Sigma-Aldrich) for 30 min, an effective time for this drug adopted from previous studies and upon our preliminary experiments. All mouse procedures were approved by University College London (London, UK) and the European Molecular Biology Laboratory (Monterotondo, Italy) Ethical Committees and were in accordance with national and European regulations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, mIGF-I may repair the heart from injury through production of specific cytokines, cross-talk with the bone marrow, and recruitment of endothelial-primed cells for de novo vascularization of the myocardium. 112 These finely tuned immune responses are not taken into account during ex vivo analyses, possibly leading to confounding results. A main limitation of the in vivo data obtained with mIGF-I cardiac restricted transgenic mice is the lack of comparison with control core peptide IGF-I cardiac restricted transgenics, to study if the observed cardioprotection is due to the peculiar properties of mIGF-I isoform (Class 1 signal peptide and a C-terminal Ea extension peptide (Figure 1) in the same experimental settings.…”
Section: Growth Signaling Stress Resistance and Heart Function In Modementioning
confidence: 99%